Implementation of Deep Learning as A Strategy to Improve the Quality of Learning in the Outermost Regions - Jacobias Deferson Pingak; Karwanto; Erny Roeminingsih (EDUJAVARE: International Journal of Educational Research, 2026)
This study examines the implementation of deep learning as a strategy to improve the quality of learning at SMA Negeri 1 Lobalain and SMA Negeri 2 Lobalain, Rote Ndao Regency, East Nusa Tenggara. Using a qualitative approach with a multi-site case study design, this research focuses on the principal's strategic management in the formulation, implementation, and evaluation of deep learning. Data were collected through observation, in-depth interviews, and document study, The findings indicate that the success of deep learning implementation is largely determined by the principal's strategic management encompassing vision-mission setting, teacher capacity building, academic supervision, infrastructure provision, and continuous evaluation. Key supporting factors include leadership commitment, teacher competence, and collaborative culture, while limited teacher understanding and inadequate infrastructure remain as barriers. This study offers strategic recommendations for schools in disadvantaged, frontier, and outermost regions (3T areas) in implementing deep learning in accordance with Permendikdasmen Number 13 of 2025.